Study on the curing properties of SBR/La-GDTC/SiO_2 composites - 杨树颜 刘岚 贾志欣 贾德民 罗远芳 (Journal of rare earths, 2011)
A lanthanum glutamic dithiocarbamate（La-GDTC） was synthesized. The vulcanization kinetic and crosslinking structure of styrene butadiene rubber （SBR）/La-GDTC/silica（SiO2） composites were studied via vulcanization kinetic simulation,swelling equilibrium and differential scanning calorimeter. Simulated curing parameters showed that the curing rate k2 of the SBR/La-GDTC/SiO2 composite was significantly higher than that of the SBR/La-GDTC composite. Also,swelling equilibrium test turned out that crosslinking density of SBR/LaGDTC/SiO2 composite evolved to higher level,compared to that of the SBR/La-GDTC composite. Ammonia modified swelling equilibrium interpreted both lanthanum ions and carboxyl groups could react with silanol groups of silica particles. Finally,vulcanization activation energies of SBR/La-GDTC/SiO2 composite were lower than that of SBR/La-GDTC composite,without respect to different approaches of the DSC measurement or Oscillated Disc Rheometer test. All the results showed that the lanthanum ions of La-GDTC could act as the metal ion catalyzer of sulfur vulcanization during the crosslinking process,which could be attributed to the unoccupied orbital of lanthanum ions. Therefore,a La-GDTC bridged structure between SBR and silica particles for the SBR/La-GDTC/SiO2 composite was suggested according to the experimental results.